The art of entertainment. heinz strunk’s thomas- mann-novels as humorous reflexions on age and illness - Voelk, Malte (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The paper focuses on the novels Ein Sommer in Niendorf (2022) and Zauberberg 2 (2024) by the German author, artist and musician who has been writing highly successful narrative literature under the pseudonym Heinz Strunk for over 20 years. His popularity is unusual in that it extends widely across different cultural areas – and with a type of humour that is not geared towards broad mass taste, but rather appears to be a niche genre. His last two novels borrow very openly from the work of Thomas Mann. This is taken as an opportunity here to explore the relationship between popular entertainment literature and culture, traditional high literature and humour theory. To narrow the focus, the motifs of age and illness, which are present throughout, are examined.
Keywords: Heinz Strunk; Thomas Mann; humour; entertainment; illness; age